EL PODER DE LA PALABRA Y LA MIRADA EN CARMEN DE MÉRIMÉE - Baynat Monreal, Mª Elena (Anales de Filología Francesa, 2007)
The originality of Mérimée in Carmen is doubtless: the writer has demonstrated that can be said much with few words. Ace in this work the author has been able to create a complex and diabolic seductive feminine personage, a type that has transferred all the borders and that an at the referring present time has supposed and supposes abroad an obligatory one for the image of Spanish woman; and all it in a brief story of not more of one hundred pages: everything a challenge. The personage of Carmen is psychotically demolishing: the gypsy woman exerts an extraordinary power on all those that surround to which uses depending of their own convenience and is dangerously seductive; Mérimée grants two powerful been marksmen to him of seduction with great teacher: the glance and the word. Carmen, prototype of the fatal woman, seduces with his extraordinary appearance, that is reduced mainly to its glance, a glance that speaks and act. On the other hand, Mérimée grants to the gypsy a viperine language that when it uses poisons and enchants such a serpent. We will analyze then this game of cautious and this vocabulary handling, the two arms of woman of the personage of Carmen that make of her an universal literary type and without equals or sticks any the text to translate.